Analisis Profil Ketangguhan Akademik Mahasiswa Universitas Muhammadiyah Tasikmalaya - Muhajirin, Muhammad; Rahimsyah, Anandha Putri (Indonesian Journal of Educational Counseling, 2025)
This research was conducted due to students' inability to cope with difficulties in the educational process. The study aims to provide an overview of the academic hardiness levels of students at Universitas Muhammadiyah Tasikmalaya. The research employed a quantitative descriptive approach. The population of the study comprised students of Universitas Muhammadiyah Tasikmalaya, with a sample size of 128 students (n=128). The instrument used was the academic hardiness scale. Validity testing was conducted using the Rasch model with the help of Winsteps software. Reliability testing was carried out using Cronbach's alpha instrument with the assistance of Winsteps software employing the Rasch model. The results showed that the items met the validity criteria of Outfit Mean Square (MNSQ): 0.5 < MNSQ < 1.5, Outfit Z-Standard (ZSTD): -2.0 < ZSTD < +2.0, and Point Measure Correlation (Pt Mean Corr): 0.4 < Pt Measure Corr < 0.85. The reliability test result was 0.97, categorized as excellent. The findings revealed that 30 students (23%) were in the high category, 98 students (77%) were in the medium category, and no students were in the low category.